ANALISIS KESALAHAN SISWA KELAS VII SMP NEGERI 19 PALU DALAM MENYELESAIKAN SOAL PERSAMAAN LINEAR SATU VARIABEL (PLSV) - Elis Safira Karindah; Dasa Ismaimuza; Rita Lefrida; Baharuddin Paloloang (Universitas Tadulako, 2025)
This study is a descriptive study with a qualitative approach that aims to describe and examine students' errors in solving linear equations of one variable (PLSV) based on Newman's stages and their causes. This data was collected through written assignments and interviews. The subjects of this study were students of class VII b at SMP Negeri 19 Palu. The informants in this study were three students of class VII b with each student having high ability, one student having medium ability, and one student having low ability at SMP Negeri 19 Palu who made the most errors. The results of this study indicate that the types of errors made by students are: (1) reading errors, (2) understanding errors, (3) transformation errors, (4) pcess skill errors, and (5) errors in writing answers. The factors causing the errors made by students are: (1) students are not careful in working on the questions. (2) students are unable to read words or recognize symbols in the questions (3) do not know the steps in solving the questions (4) students are in a hurry when solving the questions. (5) students do not understand the material being studied.